The overall and smoking-attributable burden of multiple sclerosis among older adults aged 65–89 years from 1990 to 2019 and predictions to 2040 - Su, Jiao; Liang, Yuanhao; He, Xiaofeng (Frontiers in Medicine, 2024)
Background The global prevalence of aging individuals with multiple sclerosis (MS) is increasing. This study aimed to assess the burden and trends of overall and smoking-attributable MS in older adults aged 65–89 years at the global, regional, and national levels. Methods The number and rates of years of life lived with disability (YLD) and years of life lost (YLL) due to MS for older adults in 204 countries and territories from 1990 to 2019 were retrieved from the Global Burden of Disease (GBD) Study 2019. Estimated annual percentage change (EAPC) in the age-standardized YLD and YLL rates were calculated to quantify the temporal trends. The Bayesian age-period-cohort model was used to predict the trends from 2020 to 2040. Results In 2019, there were an estimated 80,040 (95% uncertainty interval 57,534 to 103,608) YLD and 139,132 (107,632 to 161,172) YLL caused by MS among older adults globally. The age-standardized YLD and YLL rates decreased by an average of −0.21% (95% CI –0.26 to −0.16) and − 0.2% (95% CI –0.26 to −0.14) per year for overall MS from 1990 to 2019, respectively. The number of YLL globally in 2019 was 7,891 (5,003 to 10,991) and 15,667 (10,833 to 20,076) due to smoking-attributable MS. The age-standardized YLD and YLL rates decreased by an annual average of −1.14% (95% CI –1.25 to −1.04) and − 1.15% (95% CI –1.27 to −1.03) for MS attributable to smoking. Although the global age-standardized rates of YLD and YLL for MS among older adults declined from 1990 to 2019, many regions showed increases. The largest increase in age-standardized YLD rate of MS was observed in East Asia (average annual change 1.62% [95% CI: 1.56 to 1.68]), while the largest increase in the age-standardized YLL rate occurred in High-income North America (1.74% [1.53 to 1.96]). Nationally, the age-standardized YLD and YLL rates for overall and smoking-attributable MS increased exponentially with increases in SDI level (all model p < 0.001). Furthermore, projections have also indicated an expected decrease in the age-standardized rates of YLD and YLL of MS in the elderly population from 2020 to 2040. Conclusion Tracking trends in MS burden among older adults provides insights into the potential shifts in disease patterns over time. The findings lay the groundwork for informed decision-making in public health and healthcare delivery, aiming to ensure that older adults with MS receive appropriate care and support.